Evaluation of traditional architecture in terms of building physics:: Old Diyarbakir houses - Sozen, Mujgan Serefhanoglu; Gedik, Gulay Zorer (PERGAMON-ELSEVIER SCIENCE LTD, 2007)
Diyarbakir is located in the southestern part of Turkey. Traditional Diyarbakir houses are successful examples of buildings adapted to a hot dry climate. This is achieved by conforming to an old style of living and by the requirements and the use of local materials. In this Study, the general architectural properties of the traditional houses of Diyarbakir, their layouts, plan types, building envelope and facade elements are evaluated in terms of building physics criteria. Today, in spite of new technological advances, techniques and materials, identical buildings are still being built, and climatic design is not considered important in Diyarbakir. As a result these buildings do not provide shade and cool spaces, and thus cause thermal discomfort, or increase in the use of energy. The aim of this study is to emphasize the importance of the features of traditional buildings in terms of designing energy efficient, to provide appropriate buildings for the environment. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: building physics; climate; design; housing; Diyarbakir; Construction & Building Technology; Engineering